(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The interaction in water of tetra ethyl ammonium bromide ((C2H5)4N(Br)), tetra propyl ammonium bromide ((CH3CH2CH2)4N(Br)) and tetrabutylammonium bromide ((CH3CH2CH2CH2)4N(Br)) with β –cyclodextrin (β -CD, cyclomaltose) (C42H70O35 ) for dilute solutions has been studied calorimetrically at the temperature 303.15 and 313.15 K. The values of enthalpy of mixing, Q, of two binary aqueous solutions of β -CD with alkyl halides at all temperatures have been fltted by the method of least squares to the equatlon Q = x1x2 [Ao + A1(x2 – x1) + A2(x2 – x1)2+ A3(x2 – x1)3], where x2 refers to the mole fraction of the alkyl halide. The results obtained have been interpreted in terms of host guest interaction.